Human resource management practices: a case of SMEs in Zimbabwe - Mapetere, Denver; Mavhiki, Gibson; Nyamwanza, Tonderayi; Mavhiki, Severino (IJECM Pub UK, 2021)
The study was motivated by the rapid growth of employment in the SME sector Zimbabwe. An average of 24.5% of the economically active persons is employed in the private sector and thus the study sort to establish the Human Resource Management practices of SMEs in Zimbabwe. Using data collected to through a Likert scale and analysed using STATA it was established that SME owner/manager are failing to adopt best practices in Human Resources Management mainly due to financial challenges. Employees in SMEs do not possess the necessary skills to perform their duties effectively. Owner/managers with previous work experience before establishing their own organisations had adopted some form of formalised HRM system after the first year of operation. SME owner/managers were encouraged to attend Human Resource Management training programmes to broaden their knowledge.